Disruption of Neurexin 1 Associated with Autism Spectrum Disorder - Kim, Hyung-Goo; Kishikawa, Shotaro; Higgins, Anne W.; Seong, Ihn-Sik; Donovan, Diana J.; Shen, Yiping; Lally, Eric; Weiss, Lauren A.; Najm, Juliane; Kutsche, Kerstin; Descartes, Maria; Holt, Lynn; et al. (American journal of human genetics, 2008)
Autism is a neurodevelopmental disorder of complex etiology in which genetic factors play a major role. We have implicated the neurexin 1 ( NRXN1) gene in two independent subjects who display an autism spectrum disorder (ASD) in association with a balanced chromosomal abnormality involving 2p16.3. In the first, with karyotype 46,XX,ins(16;2)(q22.1;p16.1p16.3)pat, NRXN1 is directly disrupted within intron 5. Importantly, the father possesses the same chromosomal abnormality in the absence of ASD, indicating that the interruption of α- NRXN1 is not fully penetrant and must interact with other factors to produce ASD. The breakpoint in the second subject, with 46,XY,t(1;2)(q31.3;p16.3)dn, occurs ∼750 kb 5′ to NRXN1 within a 2.6 Mb genomic segment that harbors no currently annotated genes. A scan of the NRXN1 coding sequence in a cohort of ASD subjects, relative to non-ASD controls, revealed that amino acid alterations in neurexin 1 are not present at high frequency in ASD. However, a number of rare sequence variants in the coding region, including two missense changes in conserved residues of the α-neurexin 1 leader sequence and of an epidermal growth factor (EGF)-like domain, respectively, suggest that even subtle changes in NRXN1 might contribute to susceptibility to ASD.